Overwinter - Pataky, Jeremy, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2015)
A debut collection from an exciting new voice in Alaska poetry, Overwinter reconciles the natural quiet of wilderness with the clamor of built environments. Jeremy Pataky's migration between Anchorage and Wrangell-St. Elias National Park inspires these poems that connect urban to rural. This duality permeates Overwinter. Moments are at turns fevered or serene. The familial and romantic are measured against the wildness of the Far North. Empty spaces bring both solace and loneliness in full. Past loves haunt the present, surviving in the spaces sculpted by language.
I. Five Parts -- Manual Labor in the Era of Delinquent Weather -- We Were Explorers Once -- Then to Now -- Reasons for a Long Stay -- Antidote -- Wood Heat -- Runoff -- II. A Brief History of Landing Here -- The Particulars of the Built Environment -- Counting Down to a Destination within Bliss -- Barometric Pressure -- Here We Are -- Fire in the Succession Zones -- From Here You Seem a Braided River -- Screen -- Aural -- III. Fata Morgana -- IV. Surveying -- Contemplation, Composition, Interpretation -- Modernity -- How the Mistress, Distressed, Insinuated Herself into Place -- Succession -- In Review -- Field Work -- V. After This Life -- Address from a Far-off Hill -- Trash Burning -- The Smallest Ice Age -- Inroad -- Ablation Zone -- Traverse -- Thumbnail Spring Song -- Sky Behind Weather -- Steeped -- The Wild Dead.
Keywords: American poetry